Peran Perempuan Sebagai Madrasah Utama dalam Mewujudkan Tujuan Pendidikan Islam - Nur Annisa Fitria (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
The study aims to examine the strategic role of women as main madrasah (the primary school) in realizing the goals of Islamic education in the context of Generation Beta, a generation that grows up in a digital ecosystem rich in technology and artificial intelligence. The approach used is a literature study with a conceptual philosophical analysis based on the Quran, Hadith, and Mark McCrindle’s generation theory. The result of the study show that the role of mothers in the digital era is not only as moral and spiritual educators but also as digital mentors who instill ethics, moral responsibility, and critical literacy towards technology. The Beta Generation, which is highly visual and adaptive but prone to screen dependency and social isolation, needs mothers who are able to balance Islamic values with digital skills. Thus, women play an important role in shaping a generation that is not only superior in technology but also has a strong foundation in Islamic faith, morals, and character, so that family education becomes the main basis for the formation of civilization in the era of artificial intelligence